Analisis Morfologi Tanaman Pisang Kepok (Musa paradisiaca Var. Balbisiana colla) di Desa Tanjung Selamat Kabupaten Labuhanbatu Selatan - Delpiana Sinta; Rosmidah Hasibuan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Tanjung Selamat Village is one of the villages in South Labuhanbatu Regency, North Sumatra Province. Tanjung Selamat Village has several types of bananas, one of which is the Kepok Banana. This study aims to determine and analyze the morphology of the Kepok Banana plant (Musa Paradisiaca Var. Balbisiana colla) in Tanjung Selamat Village, South Labuhanbatu Regency, North Sumatra Province. This type of research is descriptive qualitative by making observations with survey techniques observing the morphology of Kepok Banana plants. The technique used in collecting data by way of observation or observations and interviews. The Kepok Banana plant (Musa Paradisiaca Var. Balbisiana colla) found in the village has several characteristics and characters in the morphology of the Kepok Banana plant, starting from the stem, size, color, and roots, leaves, flowers, stems, fruit, and others. In this case the Kepok Banana plant (Musa Paradisiaca Var. Balbisiana colla) in Tanjung Selamat Village from the results of the study showed that the morphology of the Kepok Banana plant had a green color, stem diameter 24 cm wide, 227 cm high, brown roots there are white fibrous roots, leaves are dark and light green, and the edges of the leaves are flat, the tips of the leaves are rounded. The flower stalk is 7-8 cm, the color is yellowish red the flowers are white inside, the length of the fruit is 13 cm and the diameter is 3 cm.